A disturbing vulvar mass: the tip of the iceberg - Ambrosio,Bruna (2018)
Uterine fibroids are benign monoclonal tumors that originates from the smooth muscle cells of the myometrium and are the most common solid pelvic tumors in women. In the differential diagnosis of vulvar masses we should considered Bartholin's cysts or abscesses, Bartholin's tumors, fibroids (usually fibroids of the round ligament), subcutaneous lipomas, inguinal hernia or adenomegaly. With this images we present a case of a vulvar mass caused by a fibroid, probably from the round ligament, which was a tip of the iceberg of an extensive pelvic leiomyomatosis